Downregulation of PDCD4 by deSUMOylation associates with the progression of gestational trophoblastic disease. (December 2022) - Wang, Ya-Xin; Cui, Ling; Wu, Wei-Bin; Quinn, Martin John; Menon, Ramkumar; Zhao, Jiu-Ru; Zhang, Hui-Juan
Abstract: Introduction: Gestational trophoblastic disease (GTD) encompasses a range of trophoblastic disorders from hydatidiform mole (HM), to malignant gestational trophoblastic neoplasia (GTN). The exact molecular mechanisms of GTN remain unknown. Dysregulation and dysfunction of programmed cell death 4 (PDCD4)have been observed in many cancers. The roles of PDCD4 in GTD have not been previously reported. Methods: A total of 161 cases of formalin-fixed, paraffin-embedded trophoblast blocks, and 36 cases of fresh trophoblast tissues were collected, including normal first trimester placentas, HM, and invasive HM. Choriocarcinoma cells JAR and JEG-3 were employed. The expressions of PDCD4 and small ubiquitin-like modifier 2/3 (SUMO2/3) were examined by immunohistochemistry, quantitative reverse transcription PCR and Western blotting in trophoblastic tissues and cells. The relationship between SUMOylation and PDCD4 was investigated. The effects of PDCD4 on proliferation, invasion, and migration of choriocarcinoma cells were evaluated by Cell Counting Kit-8 and transwell assays post siRNA transfection. Extracellular Matrix & Adhesion Profiler PCR Array was used to screen the downstream molecules of PDCD4. Results: PDCD4 was significantly repressed in HM tissues. Loss of PDCD4 expression was demonstrated in 90% invasive HMs. Choriocarcinoma cells also displayed with suppressed PDCD4 expression. The varied expression of PDCD4 was paralleled by SUMO2/3. Inhibition of SUMOylation reduced the expression of PDCD4. Silencing of PDCD4 promoted proliferation/migration/invasion, upregulatedMMP3/MMP8/ITGB2, and downregulated TIMP1/TIMP2 in choriocarcinoma cells. Discussion: Our results suggest that reduced SUMOylation is one reason for suppressed PDCD4 in GTD. Loss of PDCD4 likely determines the malignant phenotype of GTN by dysregulating some members of the MMPs/TIMPs/integrins complex. Highlights: PDCD4 is suppressed in trophoblasts of GTD, loss of expression in most GTN. Lower SUMOylation is associated with decreased PDCD4 in trophoblasts. Silencing of PDCD4 promoted cellular proliferation, migration, and invasion. Silencing of PDCD4 downregulated MMP3/MMP8/ITGB2, and upregulated TIMP1/TIMP2.